Targeting NK Cells for Anticancer Immunotherapy: Clinical and Preclinical Approaches - Carotta, Sebastian (Frontiers in Immunology, 2016)
The recent success of checkpoint blockade has highlighted the potential of immunotherapy approaches for cancer treatment. While the majority of approved immunotherapy drugs target T cell subsets, it is appreciated that other components of the immune system have important roles in tumor immune-surveillance as well and thus represent promising additional targets for immunotherapy. Natural killer cells are the body’s first line of defense against infected or transformed cells as they kill target cells in an antigen-independent manner. Although several studies have clearly demonstrated the active role of NK cells in cancer-immune surveillance, only few clinically approved therapies currently exist that harness their potential. Our increased understanding of NK cell biology over the past few years has renewed the interest in NK cell based anti-cancer therapies, which has lead to a steady increase of NK cell based clinical and pre-clinical trials. Here, the role of NK cells in cancer immunesurveillance is summarized and several novel approaches to enhance NK cell cytotoxicity against cancer are discussed.